Comorbidity in migraine - Schoenen, Jean.; Dodick, David; Sándor, Peter S. (Chichester, West Sussex, UK : Wiley-Blackwell, 2011)
This book presents a clinically oriented approach to understanding and treating co-morbid migraine. Case vignettes and management algorithms will enhance the clinical utility of the book.
Psychiatric comorbidity in migraine / Francoise Radat, Amanda Kalaydjian, and Kathleen R. Merikangas -- Migraine and stroke / Tobias Kurth and Hans-Christophe Diener -- Cardiovascular disorders / Ann I. Scher and David W. Dodick -- Patent foramen ovale and migraine / Todd J. Schwedt and Jean Schoenen -- Co-morbidity of migraine and epilepsy / Sheryl Haut, Shira Markowitz, and Richard B. Lipton -- Migraine and other pain disorders / Lars Jacob Stovner, Knut Hagen, and Rami Burstein -- Migraine and medication overuse / Stephen D. Silberstein -- Migraine and other comorbidities : obesity, temporomandibular disorders, and contact points / Marcelo E. Bigal -- Migraine co-morbidities in children / Cicek Wober-Bingol and Andrew Hershey -- Optimal management of migraine taking into account comorbidities and 'positive side effects' / Peter S. Sandor, David W. Dodick, and Jean Schoenen.
Includes bibliographical references and index.
Print version record.
Keywords: Migraine; Comorbidity; Migraine Disorders -- epidemiology; Comorbidity; Medicine; HEALTH & FITNESS -- Diseases -- Nervous System (incl. Brain); MEDICAL -- Neurology; Comorbidity; Migraine; Electronic books